Internet Of Things (Iot)-Based Prototype For Monitoring Water Level And Turbidity In Water Tanks - INSANUDIN INSANUDIN (Universitas Mercu Buana Yogyakarta, 2025)
Water is an essential resource for human survival. Sufficient availability and good quality of water are crucial for various daily activities. Water tanks are commonly used as a storage medium for water. Weather changes, pollution, and other factors can affect water quality. Hence, continuous water level and turbidity monitoring are essential in maintaining water quality. The Internet of Things (IoT) technology has emerged as a solution for monitoring water levels and turbidity in water tanks. This system provides real-time monitoring of water conditions in the tanks via the Internet. The objective of this research was to develop a system and device that could monitor the water level and turbidity in water tanks with the assistance of a camera. The results indicated that the system could maintain the water level by activating the pump when it falls below 20% and automatically shutting it off when it exceeds 80%. Moreover, the system will automatically notify Blynk if the water turbidity exceeds 25 NTU.